2018
DOI: 10.1007/s00253-018-9204-1
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering of Cel5E from Clostridium thermocellum to improve its thermal stability and catalytic activity

Abstract: The celH gene from Clostridium thermocellum encodes a protein containing 900 residues and three components, including Cel5E, Lic26a, and carbohydrate-binding domains. Cel5E is a member of the glycoside hydrolase-5 family and is a bifunctional xylanase/cellulase enzyme. We targeted a semi-hydrophobic pocket near the Cel5E active site and theoretically screened mutated variants for enhanced levels of thermal stability. Cel5E mutations were inserted into celH by overlapping polymerase chain reaction, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Rational engineering coupled with structural analysis and functional prediction is an efficient genetic approach to optimize enzyme properties [9,10]. To date, many thermostable endoglucanases from diverse origins and GH families have been engineered to improve their specific activity and thermal stability [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Rational engineering coupled with structural analysis and functional prediction is an efficient genetic approach to optimize enzyme properties [9,10]. To date, many thermostable endoglucanases from diverse origins and GH families have been engineered to improve their specific activity and thermal stability [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Two single mutations, Y30F and Y173F, increased the enzyme’s specific activity toward using carboxymethylcellulose sodium (CMC-Na) by 1.4- and 1.9-fold, respectively. Torktaz et al (2018) engineered Cel5E from Clostridium thermocellum by rational mutagenesis and found that individual mutations N94W, N94F, E133F and N94A improved activity on carboxymethyl cellulose (CMC) and barley β-glucan by 1.1- to 1.9-fold. As a final example, Aich and Datta (2020) reported a 2-fold increase in catalytic activity on CMC by engineering conserved residues in the substrate-binding tunnel and on the surface of a thermostable GH7 endoglucanase from Bipolaris sorokiniana .…”
Section: Protein Engineering Of Cellulolytic Enzymesmentioning
confidence: 99%